(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Abstract: In this paper, its purpose was to select and propose an applicable method for the extraction of zinc and lead from sphalerite concentrate direct leaching residue. A large number of experiments were conducted to extract zinc and lead from sphalerite concentrate direct leaching residue by hydrochloric acid and sodium chloride solution as leachant. The main optimum parameters were determined, such as liquid-solid ratio of 17.5-1, reaction temperature of 85 °C, initial hydrochloric acid concentration of 1.3 mol/L, initial sodium chloride concentration of 300 g/L, reaction time of 60 min. 95.5% of zinc, 96.0% of iron and 93.7% of lead were extracted into leachate at the optimum conditions. The lead in the leachate was in the form of [PbCl4]2-. And after the leachate was purified to remove impurities, it was converted into lead oxalate by sodium oxalate as precipitant. Finally lead oxalate was decomposed to obtain lead oxide powders via a high temperature calcination process.